Supporting innovation and the use of technologies in accountability in itiatives: lessons from Making All Voices Count - Edwards, Duncan; Hudson, Hannah; Anderson, Colin; McGee, Rosemary; Brock, Karen (IDS, 2018)
Making All Voices Count was an international initative that harnessed the power of innovation and new technologies to support effective, acc ountable governance. Focusing on six countries in Africa and Asia, the programme was implemented by a consortium of implementing partners, a nd used funding from four donors to make grants to support new ideas t hat amplified the voices of citizens, and enabled governments to liste n and respond. From the start, Making All Voices Count was also a lear ning programme. The objective of this learning was not only to bring a bout change during the programme’s life cycle, but also to leave a leg acy that would help to ensure that future governance programmes and in itiatives seeking to capitalise on the transformative potential of inn ovation and technology are more informed, inclusive and impactful. Thi s programme learning report emerged from a wider process of analysing, discussing and synthesising the data and learning from the programme, which wove together evidence-based learning about technology for acco untable governance initiatives with experiential learning on how best to support such work. The report highlights five of the lessons learne d from Making All Voices Count about how – and how not – to run large, complex programmes that intend to support innovation in governance.